EXTRACTION OF OMEGA-3 FATTY ACID FROM KILKA FISH OIL - A. Salmani; M. Rezaeian; S. Gholamipor; R. Safari; R. Porgholam (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2008)
Extraction of omega-3 fatty acids from Kilka fish oil was conducted at the laboratory scale. Extraction and purification of raw and refined Kilka oil were done in three temperatures (1,-5 and -10°C) using urea complex method. The results indicated that maximum extraction of fatty acids were achieved at 1°C and during the experiment, omega-3 ratio was increased while the saturated fatty acid and long chain menstruated fatty acids were decreased. The mean value of omega-3 acids for the refined and raw fish oil was 29.28% and 26.05% respectively. The extraction and purification t increased omega-3 fatty acids in the refined and raw fish oil to 79.8% and 68.9% respectively. Moreover, the maximum rate of pure fatty acids was also 80.51% and 69.29%. The statistical analysis showed that omega-3 ratio before and after extraction as well as purification, were significantly different (P<0.04 for raw and P<0.03 for refined fish oil). In conclusion, we can say that the fatty acids purification by urea complex was fully successful and it has the potential to be used in fish oil extraction pilot plants.